Histological evaluation of symptomatic ossification of the anterior longitudinal ligament treated with etidronate disodium: a case report. (December 2016) - Sugimura, Yusuke; Miyakoshi, Naohisa; Kasukawa, Yuji; Hongo, Michio; Shimada, Yoichi
Abstract Background Here we report the first autopsied case involving pathological examination after two resections of symptomatic ossification of the anterior longitudinal ligament with anterior osteophytes and etidronate treatment with more than 8 years of follow-up. Case presentation A 51-year-old Japanese man complained of severe dysphagia due to esophageal compression by ossification of his anterior longitudinal ligament with anterior cervical osteophytes. Although surgical removal of the anterior cervical osteophytes was performed following etidronate treatment (800 mg/day for 6 months), dysphagia occurred secondary to recurrent ossification of his anterior longitudinal ligament with anterior osteophytes 7 years after the initial resection. A second resection of the anterior cervical osteophytes was performed, and cyclic administration of etidronate disodium (1000 mg/day, 3-month administration and 3-month cessation) did not result in re-outgrowth of ossification of his anterior longitudinal ligament with anterior osteophytes. At 1 year and 6 months after the second surgery, he suddenly died. The pathological findings associated with the ossification of his anterior longitudinal ligament during etidronate therapy showed no recurrence of ossification of the anterior longitudinal ligament with anterior osteophytes. Conclusion A recurrence of ossification of the anterior longitudinal ligament with anterior osteophytes formation, which caused dysphagia, was not observed with the cyclic administration of etidronate disodium at a dose of 1000 mg/day every 3 months for a period of 1 year and 5 months in the present case.